Improving Job Satisfaction and Organizational Commitment: Analysis of the Effects of the Principal Transformational Leadership - Novitasari, Dewiana (Dinamika Pendidikan, 2020)
This study aimed to measure the effect of dimensions of transformational leadership (i.e., idealized influence, inspirational motivation, intellectual stimulation and individualized consideration) on organizational commitment of the teachers of four private vocational school in Tangerang which are mediated by job satisfaction. Data collection was done by simple random sampling to 175 population of lecturers. The returned and valid questionnaire results were 131 samples. Data processing was used SEM method with Smart PLS 3.0 software. The results of this study concluded: first, the dimensions of transformational leadership: idealized influence, intellectual stimulation and individualized consideration have positive and significant effect on job satisfaction, except inspirational motivation. Second, the dimensions of transformational leadership: idealized influence, inspirational motivation, and individualized consideration have not significant effect on organizational commitment, except intellectual stimulation. Third, job satisfaction have a positive and significant effect on organizational commitment. Fourth, the dimensions of transformational leadership: idealized influence, intellectual stimulation and individualized consideration have positive and significant effect on organizational commitment through job satisfaction as mediation, but inspirational motivation have not significant effect on organizational commitment through job satisfaction as mediation. This research could pave the way to improve the lecturer readiness in facing the era of education 4.0.